THE INFLUENCE OF MOTIVATION, PERCEIVED VALUE, AND EXPERIENCE ON REVISITING INTENTION (A STUDY AT CIPUTRA WATERPARK SURABAYA) - Izza, Neny Muthiatul (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the influence of motivation, perceived value, and experience on the revisiting intention to Ciputra Waterpark Surabaya. The sample this explanatory research is 150 respondents taken from the population of visitors of Ciputra Waterpark Surabaya. Using purposive sampling technique, the criteria of the sample are people who are at least 17yeras of age and have visited Ciputra Waterpark Surabaya at least once.The tools used to test research instrument are validity test, reliability test, and classical assumption test. The data were analyzed through multiple linear regression analysis. The goodness of fit model uses f test, and the hypothesis were tested through t test using SPSS 21. The F test result shows that motivation, perceived value, experience significantly influence revisit intention. Based on the T test result, it is found that motivation, experience, and perceived value have an effect on revisit intention.Keyword: Motivation, Perceived Value, Experience, Revisit Intention